Progress in theoretical biology. - Rosen, Robert, 1934-1998 (Academic Press, 1981)
Progress in Theoretical Biology, Volume 6 covers the theoretical analysis of biological phenomena. The book discusses the potentials in chemical systems far from thermodynamic equilibrium, particularly the reduction of reaction-diffusion systems to catastrophe theory; and a form of logic suited for biology. The text describes the order-disorder transitions in polyelectrolytes and the chaos in systems in population biology. An artificial cognitive-plus-motivational system and pattern generation in networks are also encompassed. Biophysicists and physiologists will find the book invaluable.